PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN MINAT BELAJAR PKN SISWA KELAS V SD NEGERI 008 BUKIT KAYU KAPUR - Ahmad Guantoro (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2017)
The background of this study is the low interest in learning civics class V students SD Negeri 008 Bukit Kayu Kapur. It is caused by: (a) very few number of students active during the learning process by using group work; (b) the need for students to ask questions or submit proposals to the lack of teachers is organized so that the impression received by the students are less significant; (c) although the number of students is ideal, but the enthusiasm of students in learning is still less visible, especially at the time of the question and answer; (D) of the 23 students were only 11 or 47.8% of students are serious in taking into account the subject matter of civic education takes place, whereas other students do not pay attention to lessons with enthusiasm; and (e) although the teacher has done a variety of ways, but have not been able to increase students' interest in learning, meaning ways done to date has not brought significant progress to increase their interest in learning. For that conducted the research with the aim to increase students' interest in learning civics through the implementation of cooperative learning model STAD. This classroom action research conducted in SDN 08 Bukit Kayu Kapur, the research was conducted pad from January to June 2009. The subjects were fifth grade students of SD Negeri 008 Bukit Kayu Kapur amounting to 23 students. Parameters measured research is student interest, teacher and student activity. Results showed that student interest has increased in the first cycle average student interest obtained a score of 86 (62.60%), the second cycle increased by an average score of 108 (78.30%). Additionally teacher activity also increased, in the first cycle average teacher activity score was 30 (67.00%), increased in the second cycle with an average score of activity of teachers and 38 (84.00%). Student activity also increased in the first cycle an average score of student activity is, increased in the second cycle with an average score of 164 (79.10%). It can be concluded from the results of class V students studying civics A SDN 08 Bukit Kayu Kapur can be increased through the implementation of cooperative learning model STAD.